Stabilization of the Ternary Eutectic Growth in Additively Manufactured Al-Ni-Ce Alloys - Boussinot, Guillaume; Cazic, Ivan; Döring, Markus; Schmidt, Michael; Apel, Markus (Advanced Engineering Materials, 2024)
Coupled eutectic growth is known to favor enhanced materials’ mechanical properties, owing to the small-scale composite microstructure that it produces upon solidification. Herein, the stabilization of ternary coupled growth of the three solid phases fcc-Al, (Formula presented.) Ni, and (Formula presented.) (Formula presented.) in the Al-Ni-Ce ternary alloy is studied. The four alloys under laser powder bed fusion conditions are experimentally investigated and phase-field simulations that are useful to understand qualitatively the solidification path are performed. The results tend to confirm the presence of a skewed coupled zone for the ternary coupled growth, and that this coupled zone exists for nominal compositions of the alloy around the equiatomic Al-xNi-xCe. The value of x should then increase with the solidification velocity for ternary coupled growth to occur.
CRIS-Team Scopus Importer:2024-11-08
Keywords: eutectic coupled growths; laser powder bed fusion; phase-field method